2020
DOI: 10.1007/s12032-020-01406-5
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 and cancer care: what do international guidelines say?

Abstract: Cancer patients are at particular risk from COVID-19 since they usually present multiple risk factors for this infection such as older age, immunosuppressed state, comorbidities (e.g., chronic lung disease, diabetes, cardiovascular diseases), need of frequent hospital admissions and visits. Therefore, in the COVID era, oncologists should carefully weigh risks/benefits when planning cancer therapies and follow-up appointments. Recently, several scientific associations developed specific guidelines or recommenda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
41
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 12 publications
(13 reference statements)
2
41
0
2
Order By: Relevance
“… 24 Some studies also found that patients with malignancy were especially vulnerable to COVID-19 because they generally had multiple risk factors for this infection, such as advanced age. 25 In the present study, we also found malignancy (OR 2.45; p =0.025) was independently associated with the hospitalization of the patients.…”
Section: Discussionsupporting
confidence: 72%
“… 24 Some studies also found that patients with malignancy were especially vulnerable to COVID-19 because they generally had multiple risk factors for this infection, such as advanced age. 25 In the present study, we also found malignancy (OR 2.45; p =0.025) was independently associated with the hospitalization of the patients.…”
Section: Discussionsupporting
confidence: 72%
“…The most important point of the survey was to assess how the SARS-COV-2 pandemic would influence choice and decisions for treatment in NET patients. Risk assessments of treatments have been published by medical societies for other tumor entities [4]. Only recently, some general recommendations for NET patients have been published by an expert group [15].…”
Section: Discussionmentioning
confidence: 99%
“…Cancer patients are at high risk for a severe course of COVID-19 due to several factors such as immunosuppressed state, higher age and comorbidities (e.g., chronic lung disease, diabetes, cardiovascular diseases). Therefore, in the COVID-19 era, oncologists should carefully weigh risks/benefits when planning cancer therapies and follow-up appointments [4].…”
Section: Introductionmentioning
confidence: 99%
“…Bu pro-inflamatuvar sitokinlerin yüksek seviyede salınımı da sitokin fırtınasının gelişimine ve dolayısıyla akut solunum sıkıntısı sendromu (ARDS) ile ölüme neden olmaktadır (18). (46)(47).…”
Section: Koronavirüs Ailesi Ve Covid-19unclassified